Recent Outcomes of Surgical Redo Aortic Valve Replacement in Prosthetic Valve Failure - Kang, Yoonjin; Soehartono, Nazla Amanda; Choi, Jae Woong; Kim, Kyung Hwan; Hwang, Ho Young; Kim, Joon Bum; Kim, Hong Rae; Lee, Seung Hyun; Cho, Yang Hyun (The Thoracic and Cardiovascular Surgeon, 2024)
Background As redo surgical aortic valve replacement (AVR) is relatively high risk, valve-in-valve transcatheter AVR has emerged as an alternative for failed prostheses. However, the majority of studies are outdated. This study assessed the current clinical outcomes of redo AVR.Methods and Results This study enrolled 324 patients who underwent redo AVR due to prosthetic valve failure from 2010 to 2021 in four tertiary centers. The primary outcome was operative mortality. The secondary outcomes were overall survival, cardiac death, and aortic valve-related events. Logistic regression analysis, clustered Cox proportional hazards models, and competing risk analysis were used to evaluate the independent risk factors. Redo AVR was performed in 242 patients without endocarditis and 82 patients with endocarditis. Overall operative mortality was 4.6% (15 deaths). Excluding patients with endocarditis, the operative mortality of redo AVR decreased to 2.5%. Multivariate analyses demonstrated that endocarditis (hazard ratio [HR]: 3.990, p = 0.014), longer cardiopulmonary bypass time (HR: 1.006, p = 0.037), and lower left ventricular ejection fraction (LVEF) (HR: 0.956, p = 0.034) were risk factors of operative mortality. Endocarditis and lower LVEF were independent predictors of overall survival.Conclusion The relatively high risk of redo AVR was due to reoperation for prosthetic valve endocarditis. The outcomes of redo AVR for nonendocarditis are excellent. Our findings suggest that patients without endocarditis, especially with acceptable LVEF, can be treated safely with redo AVR.
Keywords: aortic valve; aortic valve replacement; prosthesis